Targeting Cytokine Release Through the Differential Modulation of Nrf2 and NF-κB Pathways by Electrophilic/Non-Electrophilic Compounds - Fagiani, Francesca; Catanzaro, Michele; Buoso, Erica; Basagni, Filippo; Di Marino, Daniele; Raniolo, Stefano; Amadio, Marialaura; Frost, Eric H.; Corsini, Emanuela; Racchi, Marco; Fulop, Tamas; Govoni, Stefano; et al. (Frontiers in Pharmacology, 2020)
The transcription factor Nrf2 coordinates a multifaceted response to various forms of stress and to inflammatory processes, maintaining a homeostatic intracellular environment. Nrf2 anti-inflammatory activity has been related to the crosstalk with the transcription factor NF-κB, a pivotal mediator of inflammatory responses and of multiple aspects of innate and adaptative immune functions. However, the underlying molecular basis has not been completely clarified. By combining into new chemical entities, the hydroxycinnamoyl motif from curcumin and the allyl mercaptan moiety of garlic organosulfur compounds, we tested a set of molecules, carrying (pro)electrophilic features responsible for the activation of the Nrf2 pathway, as valuable pharmacologic tools to dissect the mechanistic connection between Nrf2 and NF-κB. We investigated whether the activation of the Nrf2 pathway by (pro)electrophilic compounds may interfere with the secretion of pro-inflammatory cytokines, during immune stimulation, in a human immortalized monocyte-like cell line (THP-1). The capability of compounds to affect the NF-κB pathway was also evaluated. We also assessed the compounds-mediated regulation of cytokine and chemokine release by using Luminex X-MAP® technology in human primary peripheral blood mononuclear cells (PBMCs) upon LPS stimulation. We found that all compounds, also in the absence of electrophilic moieties, significantly suppressed the LPS-evoked secretion of pro-inflammatory cytokines such as TNFα and IL-1β, but not of IL-8, in THP-1 cells. A reduction in the release of pro-inflammatory mediators similar to that induced by the compounds was also observed after siRNA mediated-Nrf2 knockdown, thus indicating that the attenuation of cytokine secretion cannot be directly ascribed to the activation of Nrf2 signaling pathway. Moreover, all compounds, with the exception of compound 1, attenuated the LPS-induced activation of the NF-κB pathway, by reducing the upstream phosphorylation of IκB, the NF-κB nuclear translocation, as well as the activation of NF-κB promoter. In human PBMCs, compound 4 and CURC attenuated TNFα release as observed in THP-1 cells, and all compounds acting as Nrf2 inducers significantly decreased the levels of MCP-1/CCL2, as well as the release of the pro-inflammatory cytokine IL-12. Altogether, the compounds induced a differential modulation of innate immune cytokine release, by differently regulating Nrf2 and NF-κB intracellular signalling pathways.